Łagodna nawracająca cholestaza wewnątrzwątrobowa - Lipiński, Patryk; Pawłowska, Joanna; Jankowska, Irena (Pediatria Polska - Polish Journal of Paediatrics, 2017)
The article constitutes an up-to-day overview on pathogenesis, clinical manifestation and treatment of benign recurrent intrahepatic cholestasis in children.